Numerical Modeling Of Pressure Source Of Sinabung Volcano Based On GPS Data In 2011-2012 Using Particle Swarm Optimization (PS0) - Kumalasari, Ratih; Srigutomo, Wahyu; Meilano, Irwan; Gunawan, Hendra (Computational And Experimental Research In Materials And Renewable Energy, 2020)
Mogi Model with particle swarm optimization (PSO) scheme have been applied to the local GPS data of Sinabung Volcano during 2011 to 2012 to receive subsurface parameters as pressure sources in terms of misfit and inversion model parameter. The size of displacement was inverted by PSO. From the inversion concluded that the position pressure source showing shallow magma pockets at a depth between ±1.3 km volume change around +0.95x106 m3 . It indicates the presence of a huge magma supply and continuous into shallow magma chamber up to the surface of Sinabung Volcano.